Assessment of children's snack foods in the Philippines - Retreta, Rosalie Pacaigue (2005)
ABSTRACT The study primarily involved a survey of snack food labels usually consumed by and marketed to the Filipino children. Only savory snacks were taken into consideraion - potato chips, corn chips and other extruded snacks, nuts. The selected products were evaluated in terms of compliance of the food manufacturers with the mandatory labeling requirements existing in the country. The products were also examined based on their composition - ingredients used and presence of food additives. Nutritional information, claims and other relevant information were also examined. The food manufacturers of the products involved in the study complied with the local mandatory labeling requirements. Most of the samples contained nutritional information on their labels. Several samples were fortified with vitamins and minerals and contained the Department of Health's Sangkap Pinoy Seal. Among the fortificants used, vitamin A, iron and calcium were predominant. The study also revealed the widespread use of monosodium glutamate and artificial flavors and colorings. The food additives contained in the samples however are classified as generally safe for consumption. Few samples display unique selling proposition that will attract specifically the children to consume these goods.